Majalah dan Perbudakan: Keabsahan Hadis dalam Soeara Moehammadijah Pra-Kemerdekaan: Magazines and Slavery: The Validity of Hadith in "Soeara Moehammadijah" Pre-Independence - Firman, Firman; Nasution, Sukma Dahlia; Azzahra, Annisa Fitri; Wendry, Novizal (El-Sunan: Journal of Hadith and Religious Studies, 2024)
This study explores the role of the Soeara Moehammadijah magazine in disseminating Islamic religious teachings and fostering the spirit of independence during the Dutch colonial period, with a particular focus on its views on slavery. The magazine is selected as the primary subject due to its significant impact on spreading Islamic values, using hadiths as supporting evidence. The research employs archival and library investigations, utilizing contemporary sources to describe the historical context. Additionally, the Takhrij method is applied, using the Kanzul Ummal book to trace the original sources of the hadiths. The objective is to rediscover the original texts and evaluate the quality of the hadiths used by Soeara Moehammadijah to support arguments on slavery. The findings indicate the use of five hadiths in the article "Pemboedakan (Slavernij) di loear dan di dalam islam" by Abdullah Harharah, with varying grades of authenticity: Khatib al-Baghdadi's chain is graded as Hasan Li Ghairihi, Ibn Asakir's as Dhaif, Imam Bukhari's as Sahih, Imam Muslim's as Sahih, and Abu Nu’aim's as Dhaif. The study reveals that Harharah’s selection of hadiths to support the independence movement often deviated from the original texts, leading to omissions, modifications, and additions in both the chain of transmission (sanad) and the content (matn) of the hadiths. ABSTRAK Penelitian ini mengeksplorasi peran majalah Soeara Moehammadijah dalam menyebarkan ajaran agama Islam dan menumbuhkan semangat kemerdekaan selama masa kolonial Belanda, dengan fokus khusus pada pandangannya tentang perbudakan. Majalah ini dipilih sebagai subjek utama karena pengaruhnya yang signifikan dalam menyebarkan nilai-nilai Islam, menggunakan hadis sebagai bukti pendukung. Penelitian ini menggunakan metode investigasi arsip dan perpustakaan, memanfaatkan sumber-sumber yang menggambarkan konteks sejarah saat itu. Selain itu, metode Takhrij diterapkan dengan menggunakan kitab Kanzul Ummal untuk melacak sumber asli dari hadis-hadis tersebut. Tujuannya adalah untuk menemukan kembali teks asli dan mengevaluasi kualitas hadis-hadis yang digunakan oleh Soeara Moehammadijah untuk mendukung argumen tentang perbudakan. Temuan menunjukkan penggunaan lima hadis dalam artikel "Pemboedakan (Slavernij) di loear dan di dalam Islam" oleh Abdullah Harharah, dengan variasi derajat keaslian: sanad Khatib al-Baghdadi dinilai sebagai Hasan Li Ghairihi, Ibn Asakir sebagai Dhaif, Imam Bukhari sebagai Sahih, Imam Muslim sebagai Sahih, dan Abu Nu’aim sebagai Dhaif. Studi ini mengungkapkan bahwa pemilihan hadis oleh Harharah untuk mendukung gerakan kemerdekaan sering kali menyimpang dari teks asli, yang mengakibatkan penghilangan, modifikasi, dan penambahan dalam sanad dan matn hadis.